"Finally, I belong somewhere I can be proud of" – Experiences of being a Clubhouse member in Norway. Issue 1 (1st January 2020) - Fekete, Orsolya Reka; Langeland, Eva; Larsen, Torill M. B.; Kinn, Liv Grethe
ABSTRACT: Purpose : The number of psychosocial Clubhouses is growing rapidly in Norway. However, more knowledge is needed about the subjective experience of Clubhouse members in terms of their recuperation processes and experiences in the Clubhouse context. Therefore, this qualitative study explored what it is like to be a Clubhouse member in Norway, and further discuss it in light of the theory of Salutogenesis on successful pathways to coping and well-being. Methods : Using a hermeneutic–phenomenological approach, the present study included in-depth, semi-structured individual interviews with 18 Clubhouse members from three accredited Norwegian Clubhouses. Analysis was conducted using systematic text condensation. Results : Three main themes emerged from the analysis: "Finally, I belong somewhere I can be proud of, " "I feel more like an ordinary citizen, just different, " and "I feel somewhat equal to others." Overall, the participants experienced improved mental and social well-being owing to their membership of a Clubhouse. Conclusions : Our findings correspond with previous international research. Owing to the positive effect participation in the Clubhouse seem to have on members' motivation, Salutogenesis might help explain helpful processes within the model. Moreover, the model might be a relevant example for policy and service development in mental health care and the labour market.